Development of a Click Beetle Luciferase Reporter System for Enhanced Bioluminescence Imaging of Listeria monocytogenes: Analysis in Cell Culture and Murine Infection Models - Ur Rahman, Sadeeq; Stanton, Michael; Casey, Pat G.; Spagnuolo, Angela; Bensi, Giuliano; Hill, Colin; Francis, Kevin P.; Tangney, Mark; Gahan, Cormac G. M. (Frontiers in Microbiology, 2017)
Listeria monocytogenes is a Gram-positive facultative intracellular pathogen that is widely used as a model organism for the analysis of infection biology. In this context, there is a current need to develop improved reporters for enhanced bioluminescence imaging of the pathogen in infection models. We have developed a click beetle red luciferase (CBR-luc) based vector (pPL2CBRopt) expressing codon optimized CBR-luc under the control of a highly expressed Listerial promoter (PHELP) for L. monocytogenes and have compared this to a lux-based system expressing bacterial luciferase for bioluminescence imaging of the pathogen using in vitro growth experiments and in vivo models. The CBR-luc plasmid stably integrates into the L. monocytogenes chromosome and can be used to label field isolates and laboratory strains of the pathogen. Growth experiments revealed that CBR-luc labelled L. monocytogenes emits a bright signal in exponential phase that is maintained during stationary phase. In contrast, lux-labelled bacteria produced a light signal that peaked during exponential phase and was significantly reduced during stationary phase. Light from CBR-luc labelled bacteria was more efficient than the signal from lux-labelled bacteria in penetrating an artificial tissue depth assay system. A cell invasion assay using C2Bbe1 cells and a systemic murine infection model revealed that CBR-luc is suited to bioluminescence imaging approaches and demonstrated enhanced sensitivity relative to lux in the context of Listeria infection models. Overall, we demonstrate that this novel CBR reporter system provides efficient, red-shifted light production relative to lux and may have significant applications in the analysis of L. monocytogenes pathogenesis.